RARE-50. PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA – OUTCOMES IN THE 'HAEMATOLOGY ERA'. (11th November 2019) - Kumar, Siddhant; Islim, Abdurrahman; Smith, Jeffrey; Haylock, Brian; Shenoy, Aditya; Husband, David; Mills, Samantha; Brodbelt, Andrew; Chavredakis, Emmanuel; Lawson, David; Jenkinson, Michael
Abstract: BACKGROUND: Primary CNS lymphoma (PCNSL) requires a biopsy for diagnosis. Administration of corticosteroids can lead to inconclusive results and delay diagnosis. The aim of this study was to compare outcomes of patients treated under haematology compared to radiation oncologists. METHODS: Retrospective case review of patients treated under radiation oncology (2006–2010) and haematology (2011–2016). RESULTS: 121 cases were identified (median age 63 years; range 19–84). Median WHO performance status (PS) was 1. Fourteen patients (11.6%) required repeat biopsy. 10 patients were managed palliatively due to poor PS. 67 cases were managed under haematology. Median symptom duration was 28 days (range 2–540). Median time from MRI to diagnosis was 18 days (range 6–232). 66 patients received chemotherapy, 1 received radiotherapy. Median overall survival (OS) was 8 months (95%CI:0.7–15.3), 5-year OS was 22.4%. 44 cases were managed under radiation oncology. Median symptom duration was 28 days (range 2–365). Median time from MRI to diagnosis was 16 days (range 6–309). 34 patients received radiotherapy first-line, 10 received chemotherapy. Median OS was 7 months (95%CI:0–21.5), 5-year OS was 15.9%. Multivariate analysis demonstrated PS (HR 2.02 (95%CI: 1.08–3.76)) and symptom duration (HR 0.63 (95%CI: 0.41–0.96)) to be significant prognostic indicators for OS. CONCLUSION: The outcomes from the 'haematology era' are similar to those achieved by radiation oncologists. Delay in diagnosis leads to worse outcomes and highlights the ongoing need to streamline the patient pathway to improve outcomes.